The influence of smoking cessation on depressive symptoms in smokers with a history of major depression: a systematic review - Pedro Diogo Ferreira Barreira Jardim Nunes (2022)
The presence of depression increases the risk for smoking and vice versa, according that half of smokers seeking treatment have a history of depression. Depressive states can be provoked or exacerbated by smoking cessation and there is consistent evidence in that direction. It must be taken into account that smokers are not a homogeneous group so that it is important to develop different smoking cessation interventions for specific groups, such as people with past or current major depression. The aim of this review was to summarize the findings from published studies to reach a conclusion of which smoking cessation interventions are more efective in reducing depressive symptoms in this specific population and if smokers who successfully abstain are at risk of increased depressive symptomatology. A systematic review was conducted based on PRISMA´s guidelines. A bibliographic search was made by quering Cochrane and PubMed databases from which were included eight papers. The majority found improvement of depressive symptomatology in the subgroup of smokers who attained to stop smoking. Moreover, SSRI treatment was associated with a reduction of depressive symptoms, in particular sertraline that reached statistical significance in reducing depressive symptomatology when compared with placebo. Even though it is not possible to draw definitive conclusions, this review highlights some evidence that smoking cessation intervention may be a realistic opportunity to improve depressive symptomatology and that active intervention with SSRI may be a big aid in treatment.